2014
DOI: 10.1097/rlu.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

A Gluten-Free Vegan Meal for Gastric Emptying Scintigraphy

Abstract: Radiolabeled idli meal is a good alternative to EWS meal for routine GES, especially among patients with specific dietary restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Rice idli meal is easy to prepare, has the advantage of being gluten-free and has been established as a solid test meal for GES in earlier Indian studies. [ 17 19 ] Though guidelines recommend continuing GES study up to 4h,[ 13 18 ] we could not extend the study for 4h because of small meal size, faster GE for rice idli meal and logistic constraints. Faster GE for rice idli meal in the present study, compared to egg white-bread meal,[ 13 18 ] can be explained based on the lower protein content in the former.…”
Section: Discussionmentioning
confidence: 99%
“…Rice idli meal is easy to prepare, has the advantage of being gluten-free and has been established as a solid test meal for GES in earlier Indian studies. [ 17 19 ] Though guidelines recommend continuing GES study up to 4h,[ 13 18 ] we could not extend the study for 4h because of small meal size, faster GE for rice idli meal and logistic constraints. Faster GE for rice idli meal in the present study, compared to egg white-bread meal,[ 13 18 ] can be explained based on the lower protein content in the former.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that more than 96% of the sulfur colloid was bound to the meal at 4 h of suspension in simulated gastric fluid and concluded that radiolabeled Idli meal is a good alternative to egg white sandwich. [5] Indian Round breads (Chapati) has also been standardized in the study by Awasthi et al, results of which showed ~90% of the radiolabel remained bound to the solid phase at 3 h at all pH levels. [14] Both Idli and Chapati are widely acceptable meals in India.…”
Section: Discussionmentioning
confidence: 99%
“…The total energy of the meal was approximately 350 kcal. [4,5] The present study was carried out for a total duration of 4 h with image acquisition done for 1 min-anterior and posterior views. The images were acquired: immediately after ingestion of meal, 30 min, 1 h, 2 h, and 4 h after meal using GE NMCT 670 (integrated SPECT/CT-single photon emission computed tomography by GE Healthcare, Chicago, USA) dual-headed gamma camera with 140 keV Tc-99 m photopeak with 20% window (140keV ± 10%).…”
Section: Methodsmentioning
confidence: 99%
“…Somasundaram et al have suggested a gluten-free vegan meal for patients with dietary restrictions. Their findings are promising [23,24,25]. Despite its accuracy and conditions similar to the physiological findings, their diagnostic examination is not commonly used due to considerable costs.…”
Section: Description Of the State Of Knowledgementioning
confidence: 90%